Predictive functional control design for pneumatic actuator with stiffness characteristic - Mohd. Faudzi, Ahmad 'Athif (2013)
This paper presents a model and controller design for a pneumatic actuator system. Three control strategies of position, force and compliance control are proposed. From the compliance control, stiffness characteristic of the pneumatic actuator will be presented in real-time system. Model of the pneumatic actuator system (transfer function) is obtained from System Identification (SI) method. Next, Predictive Functional Control (PFC) with observer design is selected as the control strategy for the pneumatic system. Performance assessment of the controller is performed in MATLAB and validated through real-time experiment. Result shows that the PFC controller is adapted to the system and able to control successfully in both simulation and experiment.